2012
DOI: 10.1111/j.1744-7976.2012.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy from Mountain Pine Beetle Timber and Forest Residuals: A Cost Analysis

Abstract: INTRODUCTIONThe outbreak of mountain pine beetle (MPB) (Dendrocutonus ponderosae Hopkins) in the forests of central British Columbia (BC) is unprecedented in recorded history. Surveys indicate that over 17 million hectares (ha) of forest have been infested, and recent forecasts suggest that by 2021, 61% of the mature pine in BC could be killed (Natural Resources Canada 2011). In light of this catastrophic infestation and the associated projected fall down in harvests of timber for traditional forest products, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…We find throughout the analysis that lumber production subsidizes harvesting of bushchips for bio-energy. This subsidy is over and above any explicit subsidies to encourage bio-energy, particularly biomass burning for electricity production, a result consistent with Niquidet et al (2012). If insufficient lumber is recoverable from the pine or non-pine species in a stand, the stand will be left in the timber portfolio as it has little economic value.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…We find throughout the analysis that lumber production subsidizes harvesting of bushchips for bio-energy. This subsidy is over and above any explicit subsidies to encourage bio-energy, particularly biomass burning for electricity production, a result consistent with Niquidet et al (2012). If insufficient lumber is recoverable from the pine or non-pine species in a stand, the stand will be left in the timber portfolio as it has little economic value.…”
Section: Discussionmentioning
confidence: 67%
“…The model can easily be modified to include multiple additional geographic zones that would enable us to explore the implications of variable transportation costs and shelf life as a function of location; this is left to future research (although see Niquidet et al 2012). This could affect the conclusions significantly and thus policy related to the pine beetle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to an increase in the demand for sawmill residuals that, in turn, leads to somewhat greater output of lumber and increased demand for logs. It will also increase the demand for roadside wastes associated with harvest operations, but whether this increases removal of such wastes is questionable and a separate issue not considered here (see Niquidet et al 2012). More importantly, an increase in the demand for wood pellets will result in the re-direction of residual fibre away from particleboard, fibreboard and pulp production to its use in coal plants (Stennes et al 2010).…”
Section: ] Andmentioning
confidence: 99%
“…Using a regional wood fibre allocation model, Stennes et al (2010) showed that expanded bioenergy production in British Columbia would not use standing MPB timber directly but instead would tend to use residuals from the primary forest sector, which had the potential to harm existing users of this fibre (e.g., pulp and pellet mills) by bidding up the price of this supply. Niquidet et al (2012) investigated the feasibility of a large wood biomass-fired power plant designed to employ the beetle-killed pine in the Quesnel Forest District, a region at the heart of the MPB outbreak. The focus of their analysis was feedstock costs and showed that average delivered feedstock costs would increase significantly over the life of an electricity power generating facility.…”
Section: Canadian Applications Of Economic Analysis To Forest Insect mentioning
confidence: 99%